High resolution Ro-Vibrational analysis of C2HD3 in the region of 600 - 1150 cm-1; High Resolution Molecular Spectroscopy, HRMS 2018 - Kashirina N. V. Nadezhda Vladimirovna; Bekhtereva E. S. Elena Sergeevna; Gromova O. V. Olga Vasilievna; Bauerecker S. Sigurd; Sydow Ch. Christian; Ulenekov (Ulenikov) O. N. Oleg Nikolaevich (2018, 2018)
Title screen